Development of interactive virtual-based learning media using the rme approach on mathematics learning outcomes - astuti, puput yuli; Nuryadi (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
The research aims to generate the interactive virtual-based learning media through RME. In addition, the research aims to identify the result level of the interactive learning media. The quality criteria used based on the Nieveen criteria, which are valid, practice and effective. The type of this research is based on Borg & Gall's simply model which suitable with the research needs. The analysis data was the validity of learning media which obtained from material experts and media experts, the practically of media learning which obtained from the students 'assessment, and the effectiveness which obtained from the results of students' learning test. The results shows that the developed multimedia in learning mathematics is valid, practical and effective.